Rethinking the repression-dissent nexus: assessing Egypt's Muslim Brotherhood's response to repression since the coup of 2013. Issue 8 (17th November 2019) - al-Anani, Khalil
ABSTRACT: This article examines the repression-dissent nexus in Islamist social movements. Several studies have overwhelmingly focused on the effects of repression on protest volume, level, and tactics. However, understanding the responses of individual members to regime repression and how they relate to the movement's collective response is rarely discussed. By analysing the response of the Egypt's Muslim Brotherhood to regime repression since the coup of 2013, this article explains the effects of repression on opposition movements. It argues that to understand the impact of repression on these movements, we need to differentiate between the collective and individual responses to repression. These two levels of analysis are crucial to better understand the repression-dissent nexus. Also, the article contends that collective and individual responses to repression cannot be explained by focusing solely on the structural and institutional factors (i.e. organization, ideology, leadership, etc.). Members' personal experiences, memory, emotions, and trauma play a key role in shaping their response to repression. The article thus accounts for both the formal and informal effects of repression on Islamists.